Factors inﬂuencing behaviour to participate in Islamic microﬁnance - Maulana, Hartomi; Abdul Razak, Dzuljastri; Adeyemi, Adewale Abideen (Emerald Publishing Limited, 2018)
The purpose of this paper is to empirically examine the factors that affect Muslim customers’participation in using Baitul Maal wat Tamwil (BMT) scheme for micro-enterprises. The decomposed theory of planned behavior (DTPB) was used as the research frame work. The paper uses primary data collected by self-administered questionnaires involving a sample of 405 respondents from selected BMTs in ﬁve different regencies in East Java. Structural equation modelling was used in the analysis. This study revealed that among the three main beliefs, only perceived behavioral control toward BMT was found to have positive and significant impact on clients' participation towards BMT. With regards to antecedents' influence on their main beliefs, only perceived compatibility, perceived complexity and uncertainty and facilitating conditions were not significant. The ﬁnding of the present study could help BMT to better manage by focussing on relative advantage and behavioral control to build client relationships.